Minimally Invasive Cardiac Surgery: Removal of an Interatrial Intraseptal Bronchogenic Cyst through a Periareolar Approach. Issue 3 (May 2018) - Van Praet, Karel M.; Stamm, Christof; Sündermann, Simon H.; Meyer, Alexander; Unbehaun, Axel; Montagner, Matteo; Nazari Shafti, Timo Z.; Starck, Christoph; Jacobs, Stephan; Kempfert, Jörg
A 58-year-old white male with a history of stroke and deep vein thrombosis presented with an interatrial intraseptal mass. Cardiac-computed tomography demonstrated a thin-walled, well-demarcated cyst in the inferior border of the fossa ovalis protruding into both atria. Removal of the interatrial intraseptal cyst was performed using a minimally invasive three-dimensional endoscopic periareolar approach.